Principles of Information Security - Nguyen, Dai Tho (Khoa Quốc tế, ĐHQGHN, 2020)
The course constitutes a survey of the discipline of information security with a balanced introduction to both security management and the technical components of information security. The essentiel tenet of the course is that information security in the modern organization is a problem for management to solve, and not one that technology alone can address. In other words, an organization’s information security has important economic consequences for which management will be held accountable.